Perfluoroalkyl substances (PFAS) in beaked redfish (Sebastes mentella) and cod (Gadus morhua) from arctic fishing grounds of Svalbard - Kowalczyk, Janine; Flor, Matthias; Karl, Horst; Lahrssen-Wiederholt, Monika (Food Additives & Contaminants: Part B, 2019)
The present study gives an overview about the concentration of PFAS in liver, fillet and belly flap of beaked redfish (Sebastes mentella) and cod (Gadus morhua) caught in pristine arctic fishing grounds of Svalbard. Out of 17 analysed substances, only six perfluoroalkyl acids (PFAAs) could be detected in the fish. The most frequently quantified substances were PFOS and perfluoroundecanoic acid (PFUnA) in liver (100%) and fillet (at least 40% and 70%, respectively) of beaked redfish and cod, and in belly flap of beaked redfish (100%). Compared to cod, beaked redfish showed significant higher PFAA concentrations with highest levels in liver. Multiple comparisons of group differences for PFAA concentrations among fish species and matrices were independent of the evaluation method, but not for the PFAA-pattern analysis. The risk assessment of PFOS indicated that beaked redfish and cod caught in the Barents Sea can be a relevant exposure source for consumers.